Pembuatan Kue Lumpur dengan Substitusi Tepung Pisang Raja sebagai Makanan Selingan Tinggi Kalium untuk Penderita Hipertensi - Dony Setiawan Hendyca Putra; Priscilia Noviyanti; Heri Warsito (UrbanGreen, 2023)
Hypertension is one of the main problems in developed and developing countries. Someone who has hypertension is often associated with high levels of sodium in the body, so the body needs minerals in the form of potassium which is able to complete the function of sodium. This study aims to develop high- potassium distilled food products in the form of kue lumpur with the substitution of king banana flour for patients with hypertension. The design used in this study was a Completely Randomized Design (CRD) 4 treatment formulation of plantain flour : flour, namely 25%: 75%, 50%: 50%, 75%: 25%, and 100%: 0% with as many repetitions as many 5 times. Based on the results of the study, kue lumpur with the proportion of king banana flour 25% and wheat flour 75% produced the best kue lumpur product from the results of the organoleptic test with a mean value of 3.49 (likes), 3.44 taste (likes), aroma 3 , 17 (normal), and texture 3.84 (like). The results of the mud cake chemical test with the best treatment had 233.6 kcal of energy, protein content of 3.94%, fat 5.70%, carbohydrate 41.55%, ash 0.98%, water 47.83% and potassium 88.6 mg. The physical test results in the form of a kue lumpur texture analyzer with the best treatment that is equal to 4.06N. For one time consumption, patients are encouraged to consume 2 pieces of kue lumpur with a content of 256.96 kcal, 4.3 grams of protein, 6.27 grams of fat, 45.71 grams of carbohydrates, and 97.46 mg of potassium. Within a day, the patient will be given 2 snack meals.